(untitled) (Revista cientifica In Vestigium Ire, 2016)
In a world in which the focus shifts diametrically dizzying and the pendulum of opinion trends moving at the same speed of technological and social progress, publication No. 9 Investigium Ire Magazine offers the possibility of transcribing results questions in administrative, business and financial which I believe allows one of the best ways of transmitting knowledge towards change in many academic processes. In the Administrative and Accounting, the production of scientific knowledge is clear that we can not live without that combination of ideas and practices. Nor can we live without breathing, sleeping, relate, and not why we are satisfied everything is done. Similarly it happens with the investigation: we are immersed in it, but it is clear that we no longer understand. What we call research seems to have lost the ties that bound her with knowledge. It is not just that intellectual work is not respected, is that there is a clear sense of the role that knowledge plays in our lives. The increase in the generation of networks of knowledge, product research by the different actors in the administrative scientific and business community is heading to the link between the everyday world we live in and scientific practice, including formal action and consensus Informal and tradition. This can prove the interdisciplinary approach of our magazine, which makes it possible to distinguish new shades of vocational training, as well as removing barriers to knowledge and the unification of the different disciplines, in such a way that the understanding of social phenomena from more flexible perspectives and diverse areas of knowledge. Against this process of change is required in the Institutions of Higher Education transform and promote appropriate spaces of interdisciplinary relationships, educators, facilitators and co-authors of their development, and students who are aware that this type of training allows them to demonstrate the need for develop skills to understand and face reality in an interdisciplinary way. Achieve interdisciplinarity then seeks a brainstorming exercise in which both teachers and students rethink the paradigms and imaginary adopted as real throughout their training process and during the exercise of their profession, enabling encourage a prospective environment with greater development of thought . This time, in different sections of the magazine together professionals with different backgrounds, developed in various social contexts, with complementary studies in different areas of knowledge and not only those which generally provides the administrative area, business and accounting are given, but not assume that reality from the same perspective, they manage to be complementary. Before this presentation magazine Investigium Ire, is the result of the initiative of teachers and managers of programs in business administration, international business and public accounting, which have generated spaces for the dissemination of research work, with a great Publindex advance in step in C, with the dedication and consistent work aim to continue rising to meet the strategic planning of the Directorate in the Division of Administrative and financial Sciences. Convinced that we can allow the research community to continue the generation of new knowledge. receptivity to new or different ways of thinking in order to constantly enrich and ennoble social science disciplines and thus get their evolution in response to greater needs in new and increasingly complex contexts are expected.